PEMILU DAN POLARISASI POLITIK: TANTANGAN MEMBANGUN HARMONISASI MASYARAKAT DI DESA TONGKO KECAMATAN BAROKO PASCA PEMILIHAN BUPATI KABUPATEN ENREKANG 2024 - Afin Abrori (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2025)
Elections and Political Polarisation: The Challenges of Building Community Harmony in Tongko Village, Baroko Subdistrict after the 2024 Enrekang Regency Regent Election is an interesting issue that is increasingly being discussed by the Tongko village community. It becomes a separate question in the midst of the Tongko village community regarding the challenges of building harmonisation after the election was held. Researchers deliberately chose to examine this issue with the aim of finding out what is the root of the problem why the Regent election in Enrekang Regency this year is very heated, in addition researchers also want to know more deeply what the impact of political polarisation is and how to deal with it after the election takes place. The research method used in this research is research with a qualitative approach. The results of this study found that the root cause of why this year's regent election was so heated was because there were two pairs of candidates who were close relatives. The effects and impacts of political polarisation can create social fragmentation, disrupt daily life, decrease community credibility and have an impact on government. Therefore, among the efforts to rebuild community harmony is to instill and implement the values of Pancasila, instill and implement the harmonious values of Bhinneka Tunggal Ika, instill religious values, build dialogue spaces, parties and leaders who play an active role.